Enhanced separation of bioactive triterpenic acids with a triacontylsilyl silica gel adsorbent: from impulse and breakthrough experiments to the design of a simulated moving bed unit - Azenha, Ivo S. (2020)
A simulated moving bed (SMB) unit was designed to separate oleanolic and ursolic acids, two naturally occurring triterpenoids with structural isomerism, with remarkable nutraceutical and pharmacological properties. A triacontylsilyl silica gel adsorbent (stationary phase of an Acclaim C30 column) was considered and impulse tests with different solvents were performed to select a mobile phase, from which methanol/water 95/5 (%, v/v) emerged as the most suitable. Equilibrium and global mass transport coefficients were then determined through breakthrough experiments using pure compound solutions and the C30 column. Afterwards, these parameters were applied to the simulation of two model binary mixture separations, whose breakthrough curves were also experimentally measured. Finally, the SMB unit was designed and optimized. It was demonstrated that using the packing of an Acclaim C30 column and methanol/water 95/5 (%, v/v) as mobile phase it is possible to separate both acids with purities of 99.9 wt.%, a productivity of 1.705 kg/(m3adsorbent day), and a configuration of two columns per section (2–2–2–2). The simulated results obtained in this work with the C30 stationary phase represent a significant improvement over literature data.